Odpowiedź :
-(x+1)⁴(6-x)(5x+5)x³ > 0
(x+1)⁴(x-6)5(x+1)x³>0 /5
(x+1)⁵(x-6)x³>0
x∈(-1,0)U(6, +∞)
(x+1)⁴(x-6)5(x+1)x³>0 /5
(x+1)⁵(x-6)x³>0
x∈(-1,0)U(6, +∞)
-(x+1)⁴(6-x)(5x+5)x³ > 0
-(x+1)⁴(6-x)5(x+1)x³>0
-5(x+1)⁴(6-x)(x+1)x³>0
-5(x+1)⁵(6-x)x³>0
x=-1v x=6vx=0
wykres od gory od prawej przebija i mamy
x∈(-1,0)u(6, +∞)
-(x+1)⁴(6-x)5(x+1)x³>0
-5(x+1)⁴(6-x)(x+1)x³>0
-5(x+1)⁵(6-x)x³>0
x=-1v x=6vx=0
wykres od gory od prawej przebija i mamy
x∈(-1,0)u(6, +∞)
-(x+1)⁴(6-x)(5x+5)x³ >0
(x-1)⁴(x-6)5(x+1)x³ >0/5
(x+1)⁵(x-6)x³ >0
x∈(-1,0)U(6,+⁰⁰)
chyba tak
(x-1)⁴(x-6)5(x+1)x³ >0/5
(x+1)⁵(x-6)x³ >0
x∈(-1,0)U(6,+⁰⁰)
chyba tak